Sustainability disclosure and earnings informativeness: evidence from Sri Lanka - RM Nayana Chandani Swarnapali (Emerald Publishing Limited, 2019)
The purpose of this paper is to investigate whether the communication that takes place through the sustainability disclosure (SD) route has an effect on earnings informativeness (EI) of firms in an emerging market.The sample consists of companies listed on the Colombo Stock Exchange in Sri Lanka, where SD is a new phenomenon and a voluntary reporting initiative. Regression analysis is executed on the panel data to achieve the study objective.The result reveals a positive association between SD and EI. Sustainability reports may provide useful information that supplements merely financial data, aiding the stakeholders to interpret the financial reporting better. The finding premises that SD enhances EI, communicating value relevant information to capital market participants.SD does much to reduce capital market participants’ uncertainties, thereby aiding them to assess financial information better.The findings of the study confirm earlier research findings that indicate a positive association between SD and EI, suggesting that capital market participants are gradually becoming aware of the value relevance of sustainability reports.This is the first study investigating SD and EI association that is specific to the Sri Lankan context. Owing to the sparse studies done on the SD and EI association, this study should contribute significantly to the existing literature by broadening the geographical coverage.